Review of the state of the art of acrylamide human biomonitoring. (May 2022) - Albiach-Delgado, Abel; Esteve-Turrillas, Francesc A.; Fernández, Sandra F.; Garlito, Borja; Pardo, Olga
Abstract: Human biomonitoring (HBM) is a very useful tool for assessing human exposure to acrylamide (AA). In the framework of the Human Biomonitoring Initiative (HBM4EU) AA was included in its second list of priority substances due to the potential threat to human health. HBM data on AA are scarce, but the use of specific and sensitive biomarkers represents a reliable indicator of exposure. In this review an overview of available knowledge on HBM of AA is provided in terms of: i) preferred exposure biomarkers and matrices for the HBM of AA; ii) analytical methods for determining its biomarkers of exposure in the most used specimens; iii) current HBM data available; and iv) tools for interpreting HBM data for AA in relation to risk assessment. Finally, future trends in this field are discussed. Graphical abstract: Image 1 Highlights: Biomarkers for human biomonitoring of acrylamide have been evaluated. Analytical methods for the determination of biomarkers of acrylamide exposure have been reviewed. Reported levels of internal exposure to AA are above the health-based exposure guidelines. The risk assessment follow-up of AA exposure in the global population is necessary.